2007
DOI: 10.1104/pp.106.095273
|View full text |Cite
|
Sign up to set email alerts
|

Actin Dynamics in Papilla Cells of Brassica rapa during Self- and Cross-Pollination

Abstract: The self-incompatibility system of the plant species Brassica is controlled by the S-locus, which contains S-RECEPTOR KINASE (SRK) and S-LOCUS PROTEIN11 (SP11). SP11 binding to SRK induces SRK autophosphorylation and initiates a signaling cascade leading to the rejection of self pollen. However, the mechanism controlling hydration and germination arrest during self-pollination is unclear. In this study, we examined the role of actin, a key cytoskeletal component regulating the transport system for hydration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 57 publications
6
49
0
Order By: Relevance
“…Endomembrane breakdown in incompatible pollen tubes was found in Nicotiana (Goldraij et al, 2006) and also in Brassica, where vacuolar disruption in incompatible stigmatic papilla cells and rejection is triggered by SRK (S-locus receptor kinase) (Iwano et al, 2007). Actin depolymerization was also detected in stigmatic papilla cells (Iwano et al, 2007). These data indicate a potential link among the different SI systems.…”
Section: Do Different Si Systems Use Common Mechanisms To Reject Incomentioning
confidence: 67%
See 1 more Smart Citation
“…Endomembrane breakdown in incompatible pollen tubes was found in Nicotiana (Goldraij et al, 2006) and also in Brassica, where vacuolar disruption in incompatible stigmatic papilla cells and rejection is triggered by SRK (S-locus receptor kinase) (Iwano et al, 2007). Actin depolymerization was also detected in stigmatic papilla cells (Iwano et al, 2007). These data indicate a potential link among the different SI systems.…”
Section: Do Different Si Systems Use Common Mechanisms To Reject Incomentioning
confidence: 67%
“…The mechanisms involved in inhibition of pollen by the pear SI response shared some features with the mechanistically different SI in the poppy, where S-protein (recently renamed PrsS) triggers a Ca 2+ -dependent signal cascade, including protein phosphorylation, depolymerization of actin cytoskeleton and microtubules, and PCD (Geitmann et al, 2000;Staiger and Franklin-Tong, 2003;Thomas and Franklin-Tong, 2004;McClure and Franklin-Tong, 2006;Thomas et al, 2006;Poulter et al, 2008). Endomembrane breakdown in incompatible pollen tubes was found in Nicotiana (Goldraij et al, 2006) and also in Brassica, where vacuolar disruption in incompatible stigmatic papilla cells and rejection is triggered by SRK (S-locus receptor kinase) (Iwano et al, 2007). Actin depolymerization was also detected in stigmatic papilla cells (Iwano et al, 2007).…”
Section: Do Different Si Systems Use Common Mechanisms To Reject Incomentioning
confidence: 91%
“…The pollen surface is covered with exine and a protein-and lipid-rich substance called the pollen coat. The pollen coat alone from cross-pollen grains induced actin polymerization, while self-pollen coat alone induced the disappearance of actin bundles (Iwano et al, 2007). Furthermore, electron microscopic observation in Brassica oleracea revealed that applying the isolated pollen coat to the stigma caused cell wall expansion (Elleman and Dickinson, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we speculated that unknown molecules in the pollen grain elicit a Ca 2+ -dependent signaling pathway in the papilla cells and that preexisting molecules in the papilla cells keep intracellular [Ca 2+ ] at low levels during compatible pollination, while extracellular [Ca 2+ ] is high. Cell biological analysis of B. rapa showed that cross-pollination induced the concentration of actin bundles at the pollen attachment site, whereas self-pollination induced actin depolymerization; in addition, the actin-depolymerizing drug cytochalasin D significantly inhibited pollen germination during cross-pollination (Iwano et al, 2007). The pollen surface is covered with exine and a protein-and lipid-rich substance called the pollen coat.…”
Section: Introductionmentioning
confidence: 99%
“…In living pollen, visualization of mitochondria and plastids has been established (Matsushima et al, 2008;Tang et al, 2009), and precise monitoring of actin dynamics in papilla cells and Ca 2+ dynamics in pollen tubes is also successful in pollination studies (Iwano et al, 2007(Iwano et al, , 2009 …”
Section: Advanced Technology and Information For Geneticsmentioning
confidence: 99%